EDUCATION OF ADDITIONAL FEEDING (MT) BISCUITS TOWARDS FETAL WEIGHT IN PREGNANT MOTHERS CHRONIC ENERGY LACK AT PUSKESMAS SEI SUKA - Siti Sarah Bintang (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2022)
Chronic Energy Deficiency (KEK) is a nutritional problem caused by a lack of food consumed for a long time, a matter of years. Lack of energy intake of macronutrients (carbohydrates, protein and fat) and micronutrients, especially vitamin A, vitamin D, folic acid, iron, zinc, calcium and iodine as well as other micronutrients. The implementation of PkM activities for pregnant women is carried out through notifications via social media by filling out a google form with a sample of 20 pregnant women who are in the Work Area of the Sei Suka Health Center. The results showed that the increase in the body mass index of pregnant women who experienced SEZ increased by 65% and did not increase by 35%. There is an increase in understanding related to Education on Supplementary Food Giving (Mt) biscuits to fetal weight in chronic energy deficient pregnant women (KEK) in the Work Area of the Sei Suka Health Center